Rain Attenuation Characteristics for Earth-Space Communication in parts of Northeast and Southwest Nigeria - Igwe, Kingsley; Samuel , Victor (Journal of Advanced Industrial Technology and Application, 2025)
The characteristics of rain attenuation for earth-space communication in three Northeast States (Adamawa, Gombe and Taraba) and three Southwest States (Lagos, Oyo and Ogun) of Nigeria are presented in this paper. 33 years rainfall data obtained from the Nigerian Meteorological Agency (NiMet) was utilised. Chebil rain rate model was used to compute the point rainfall rate, while the ITU-R P.618-12 model was used to compute the rain attenuation for the six locations. The point rainfall rate computed in the Northeast ranged between 90.34 mm/h and 96.2 mm/h, while higher rainfall rates that ranged between 99.7 mm/h and 108.2 mm/h were recorded in the Southwest. Elevation angles of 23°, 42.5° and 55° were considered. The computed rain attenuation for the Northeast States ranged between 10.22 dB and 37.14 dB, while that of the Southwest States ranged between 10.60 dB and 41.00 dB for time percentage exceedance of 0.01 at Ku-band. From the values of the rain attenuation predicted, availability of signal is possible at 42.5° and 55° elevation angles but impossible at 23° elevation angle.